Characteristics of rhizobia nodulating beans in the central region of Minnesota - Bernal, G.R; Tlusty, B; Estevez de Jensen, C; van Berkum, P; Graham, P.H (Canadian journal of microbiology, 2004)
Until recently, beans (Phaseolus vulgaris L.) grown in Minnesota were rarely inoculated. Because of this, we hypothesized that bean rhizobia collected in Minnesota would either share characteristics identifiable with Rhizobium etli of Mesoamerican or Andean origin, introduced into the region as seed-borne contaminants, or be indigenous rhizobia from prairie species, such as Dalea spp. The latter organisms have been shown to nodulate and fix N 2 with Phaseolus vulgaris. Rhizobia recovered from the Staples, Verndale, and Park Rapids areas of Minnesota were grouped according to the results of BOXA1R-PCR fingerprint analysis into 5 groups, with only one of these having banding patterns similar to 2 of 4 R. etli reference strains. When representative isolates were subject to fatty acid - methyl ester analysis and 16S rRNA gene sequence analysis, the results obtained differed. 16S rRNA gene sequences of half the organisms tested were most similar to Rhizobium leguminosarum. Rhizobia from Dalea spp., an important legume in the prairie ecosystem, did not play a significant role as the microsymbiont of beans in this area. This appears to be due to the longer time needed for them to initiate infection in Phaseolus vulgaris. Strains of Rhizobium tropici IIB, including UMR1899, proved tolerant to streptomycin and captan, which are commonly applied as seed treatments for beans. Local rhizobia appeared to have very limited tolerance to these compounds.Key words: Rhizobium diversity, Phaseolus vulgaris, seed treatment, taxonomy.